Stage fright - Martin, Ann M., 1955-; Sims, Blanche (New York : Holiday House, 1984)
Shy Sara panics when her fourth-grade teacher announces that her class is to perform a play before the entire school, but eventually learns that stage fright can sometimes be healthy.
Keywords: Children's stories, American; Stage fright -- Fiction; Fear -- Fiction; Schools -- Fiction